2021
DOI: 10.1080/10508406.2021.1966633
|View full text |Cite
|
Sign up to set email alerts
|

It takes two to tango: How scientific reasoning and self-regulation processes impact argumentation quality

Abstract: Background: Improving scientific reasoning and argumentation are central aims of science education. Because of their complex nature, self-regulation is important for successful scientific reasoning. This study provides a first attempt to investigate how scientific reasoning and self-regulation processes conjointly impact argumentation quality. Methods: In a study with university students (N = 30), we used fine-grained process data of scientific reasoning and self-regulation during inquiry learning to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 105 publications
1
15
0
Order By: Relevance
“…The advantage of ENA is that the temporal patterns of individual connections can be easily captured and compared between individuals. In an exploratory think aloud study (Omarchevska et al, 2021), we found that students who were monitoring during scientific reasoning activities achieved higher argumentation quality than their peers who did not monitor using ENA. These findings demonstrated the added value of studying the temporal interaction between scientific reasoning and self-regulation processes and its effects on argumentation quality.…”
Section: Epistemic Network Analysismentioning
confidence: 83%
See 4 more Smart Citations
“…The advantage of ENA is that the temporal patterns of individual connections can be easily captured and compared between individuals. In an exploratory think aloud study (Omarchevska et al, 2021), we found that students who were monitoring during scientific reasoning activities achieved higher argumentation quality than their peers who did not monitor using ENA. These findings demonstrated the added value of studying the temporal interaction between scientific reasoning and self-regulation processes and its effects on argumentation quality.…”
Section: Epistemic Network Analysismentioning
confidence: 83%
“…For instance, students need to monitor whether they are manipulating the correct variables or how much data they need before drawing a conclusion. According to a fine-grained analysis of students' self-regulation and scientific reasoning processes monitoring during scientific reasoning activities was associated with higher argumentation quality (Omarchevska et al, 2021).…”
Section: Self-regulated Learningmentioning
confidence: 96%
See 3 more Smart Citations